Sustainability: The Myth, The Fad and The Reality - Adebayo Adepoju (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Sustainability-related challenges like climate change indices affect everything directly or indirectly whenever they strike. Given pervasive nature of sustainability challenges, nothing on the surface of the Earth is immune to them. Paradoxically, organizations, as major contributors to sustainability matters through their business operations, also remain potential victims. Therefore, embracing practices that depart from unsustainable business practices is crucial to prioritise sustainability in an organization. While some organizations are making sincere headway in this regard, others seem confused in their approaches and fail to prioritise comprehensive management orientations. Against this backdrop, the present study employs a systematic approach to literature review in view to put sustainability practices in proper perspectives and neutralize misconception concerning it toward making fair trade-offs among various goal components towards facilitating an equitable reconciliation between the two prominent stakes in business: shareholders and stakeholders. The study concludes that moving sincerely toward true sustainability practices, rather than deception, leads an organisation to become sustainability compliant. Although, the study contributes valuable insights to the literature within the domain of business and management, the researcher acknowledges several limitations, including inability to use the primary data, a mixed-method approach to data collection and statistical tool for analysis.